2009
DOI: 10.1186/bcr2262
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and assessing women at high risk for breast cancer

Abstract: There has been progress in the identification of factors that confer important risk for the development of breast cancer. The factors include: heritable mutations in susceptibility genes; exposure to therapeutic radiation during breast development (as for Hodgkin's disease survivors who received therapeutic radiation to the chest); and histologic lesions, including LCIS and atypical hyperplasias. Testing for mutations in the BRCA1 and BRCA2 breast ovarian cancer susceptibility genes has become part of the esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…36 It has been observed that approximately 80% of BRCA-1-associated breast cancers are negative for ER/PR and Her-2/neu (triple negative), and cluster with basal-like breast cancers by DNA microarray while 80% of BRCA-2-associated breast cancers are ER/PR+ but Her-2/neu negative and luminal. 37 In this study, six cases of tumor recurrence were detected in the {ER/PR(+ve), Her-2(Àve)} group, with a poor clinical out come than the {ER/ PR(+ve), Her-2(+ve)} subtype. This could be explained by the fact found in a retrospective study using 58 Her-2 amplified tumors, unsupervised gene expression analysis.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…36 It has been observed that approximately 80% of BRCA-1-associated breast cancers are negative for ER/PR and Her-2/neu (triple negative), and cluster with basal-like breast cancers by DNA microarray while 80% of BRCA-2-associated breast cancers are ER/PR+ but Her-2/neu negative and luminal. 37 In this study, six cases of tumor recurrence were detected in the {ER/PR(+ve), Her-2(Àve)} group, with a poor clinical out come than the {ER/ PR(+ve), Her-2(+ve)} subtype. This could be explained by the fact found in a retrospective study using 58 Her-2 amplified tumors, unsupervised gene expression analysis.…”
Section: Discussionmentioning
confidence: 59%
“…It has been observed that approximately 80% of BRCA-1-associated breast cancers are negative for ER/PR and Her-2/neu (triple negative), and cluster with basal-like breast cancers by DNA micro-array while 80% of BRCA-2-associated breast cancers are ER/PR+ but Her-2/neu negative and luminal. 37…”
Section: Discussionmentioning
confidence: 99%